القواعد الترجيحية المتعلقة بدلالة السياق في القرآن الكريم: Preference Rules Related to the Holly Quran Context Significance - aloodani, Abdulrahman abdo; Nashwan abdo Khaled, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يهدف البحث إلى تسليط الضوء على بعض القواعد الأساسية للترجيح بالدلالات السياقية، والتي تعين من أعملها على الوصول إلى المعاني الدقيقة للدلالات السياقية، كما أنها تبين أن إهمال مثل هذه القواعد الترجيحية أثناء الاستدلال بالدلالة السياقية من أكبر أسباب الوقوع في الأخطاء التفسيرية والتي قد ينشأ عنها ظهور بعض الأقوال الشاذة، وقد ذكر الباحثان في هذا الدراسة ألصق القواعد الترجيحية بالدلالة السياقية مع ذكر أمثلة لكل قاعدة توضّح المراد من القاعدة الترجيحية وتبيّن الطريقة التطبيقية لها وكيفية استعمالها في الأدلة القرآنية. وقد تم استخدام منهجين أساسيين لتحقيق الأهداف المحددة لهذا البحث، أولهما المنهج الاستقرائي الذي تم من خلاله التتبع لجمع هذه القواعد من مظانّها وفرزها لاستخلاص ألصقها بالدلالة السياقية المتعلقة بالقرآن الكريم، وبعد الاستقراء والاستخلاص اتبع الباحثان المنهج التحليلي وذلك من خلال تحليل هذه القواعد الترجيحية وبيان معانيها وذكر أمثلتها التطبيقية من أدلة القرآن الكريم والكشف عن العلاقة بينها وبين دلالة السياق أثناء استخدامها. ومن أبرز ما أسفر عنه البحث من نتائج بيان الأثر البالغ لهذه القواعد الترجيحية عند إعمال الدلالة السياقية، وبيان خطورة الإهمال لمثل هذه القواعد عند الاستدلال السياقي. ABSTRACT: This research aims at shedding the light on some rules of context significance preference, which result in accurate meanings of context reference, they also point out that neglecting the preference rules at context reference inference, is one of the reasons for interpretation mistakes that may result in the emergence of some irregular statements. Through the present research, I presented the preference rules for context significance, with some examples of each rule to explain the scope of the preference rule and to explain the method of application, and how to use them in the context of Quran. Two basic mythologies are applied to achieve the research objectives. Firstly, the inference methodology, for collecting, sorting and matching those rules with the Holly Quran context significance. After inference and induction, the researcher applied the analytical methodology through analyzing those preference rules, their meanings and presenting applied examples from the Holly Koran, in addition to defining the relationship between them and the context significance through using them. The research conclusions include defining the critical effect of those preference rules when using context significance, and defining the negative effect of neglecting those rules at the context inference.